Indoor radon assessment in kindergartens: towards a national action plan - Danila Carrijo da Silva Dias; Nivaldo Carlos da Silva; Wanilson Luiz Silva; Marcos Vinícius Rodrigues (Brazilian Journal of Radiation Sciences)
The study presents the results of indoor radon monitoring of 342 public kindergarten rooms of a Brazilian municipality within a region featuring high natural radioactivity. Facility characterization local perception assessment were also conducted. Rooms were monitored by exposure of ATD detectors for an average 356 days. Monitoring resulted in arithmetic and population weighted means of 83 and 82 Bq m-3 respectively, while a geometrical mean value of 61 Bq m-3 was estimated. Concentrations ranged between < 3 and 697 Bq m-3 while 8.1% of rooms presented values above 200 Bq m-3 (in different units), where similarities in construction materials used in floors were noted. High variability was observed among regions, CEI units within a region and even rooms within a unit. The collected data on room ventilation elucidated challenges to large monitoring programs when evaluating the impact of human habits and window characteristics in results. The high variability of results poses challenges to the establishment of national programs in large and diverse areas such as Brazil. The first indoor radon study in children facilities in the country represents an important step towards it.